Limited-stage small cell lung cancer: Outcomes associated with prophylactic cranial irradiation over a 20-year period at the Princess Margaret Cancer Centre. (September 2021) - Yan, Michael; Toh, Tzen S.; Lindsay, Patricia E.; Weiss, Jessica; Hueniken, Katrina; Yeung, Christy; Sugumar, Vijithan; Pinto, Dixon; Tadic, Tony; Sun, Alexander; Bezjak, Andrea; Cho, John; et al.
Highlights: Prophylactic cranial irradiation (PCI) was more commonly used in younger patients. PCI utilization rates did not change throughout our 20-year institutional experience. PCI was associated with improved OS and lower brain metastasis risk, independent of MRI follow-up or era of treatment. For LS-SCLC patients with good thoracic response, PCI remains the standard-of-care. Abstract: Background & purpose: Prophylactic cranial irradiation (PCI) is recommended for limited-stage small-cell lung cancer (LS-SCLC) patients with good response to concurrent chemoradiation. We report our institution's 20-year experience with this patient population and associated clinical outcomes. Materials & methods: A retrospective cohort of consecutive LS-SCLC patients treated with curative intent chemoradiation at our institution (1997–2018) was reviewed. Overall survival (OS) was calculated using the Kaplan-Meier method, and significant covariates determined by the Cox proportional hazards model. Covariates predictive of PCI were determined using Fisher's exact test and the Mann-Whitney test. Brain failure risk (BFR) was calculated using the cumulative incidence method treating death as a competing event. Treatment cohorts (historic vs. contemporary) were stratified by the median year of diagnosis (2005). Results: A total of 369 patients with LS-SCLC were identified, of which 278 patients were notionally PCI eligible. PCI was given to 196 patients (71%). Younger age was associated with PCI utilization (p < 0.001). PCI utilization rates did not change between the historic and contemporary treatment era (p = 0.11), whereas magnetic resonance imaging (MRI) use at baseline and follow-up became more prevalent in the contemporary era (p = <0.001). On multivariable analysis, PCI utilization was associated with improved OS (HR 1.88, 95% CI 1.32–2.69) and decreased BFR (HR 4.66, 95% CI 2.58–8.40). Patients who had MRI follow-up had a higher incidence of BFR (HR 0.35, 95% CI 0.18–0.66) in multivariable analyses. Conclusions: For LS-SCLC patients at our institution, PCI is more frequently utilized in younger patients, and the utilization rate did not change significantly over the past 20 years. PCI was independently associated with improved OS and lower BFR. Omission of PCI in LS-SCLC patients should not be routinely practiced in the absence of further prospective data.